2018
DOI: 10.3168/jds.2017-13932
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Field study to investigate the associations between herd-level risk factors for milk fat depression and bulk tank milk fat percent in dairy herds feeding monensin

Abstract: Fat is the most variable milk component, and maintaining milk fat continues to be a challenge on commercial dairy farms. Our objectives were to establish associations between herd-level risk factors for milk fat depression and bulk tank milk fat content in commercial dairy herds feeding monensin. Seventy-nine Holstein commercial dairy herds in the northeast and Upper Midwest United States were enrolled in an observational study. Data were collected on herd characteristics, total mixed ration (TMR) samples, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In our study, DIM of the experimental groups were not controlled; therefore, it is possible that at least some of the difference in FA profile of cheese between the groups could be due to the presence of a higher percentage of fresh cows in the treated group. Existing literature, however, supports the theory that monensin influences FA concentration in milk by altering ruminal microbiota (Bell et al, 2006;McCarthy et al, 2018). Odongo et al (2007) showed an increased concentration of long-chain PUFA and total MUFA in milk by 9 and 5%, respectively, in a group fed TMR + 24 mg of monensin premix per kilogram of DM compared with a control group.…”
Section: Cheese Composition and Sensory Analysismentioning
confidence: 96%
“…In our study, DIM of the experimental groups were not controlled; therefore, it is possible that at least some of the difference in FA profile of cheese between the groups could be due to the presence of a higher percentage of fresh cows in the treated group. Existing literature, however, supports the theory that monensin influences FA concentration in milk by altering ruminal microbiota (Bell et al, 2006;McCarthy et al, 2018). Odongo et al (2007) showed an increased concentration of long-chain PUFA and total MUFA in milk by 9 and 5%, respectively, in a group fed TMR + 24 mg of monensin premix per kilogram of DM compared with a control group.…”
Section: Cheese Composition and Sensory Analysismentioning
confidence: 96%
“…Milk fat production is highly variable between herds and cows within a herd due to differences in genetics, season, production level, and other factors. In a recent field study of 79 herds in the upper midwest and northeast regions of the United States, McCarthy et al (2018) reported milk fat percentage averaged 3.43, but ranged from 2.70 to 4.30; milk fat trans-10 C18:1 averaged 1.06% of milk fatty acids (FA), but ranged from 0.37 to 4.91; and FA <16 C that are de novo synthesized in the mammary gland averaged 22.5% of FA, but ranged from 17.8 to 26.1. They reported an exponential relationship between milk fat concentration and trans-10 C18:1, which is an intermediate of the alternate biohydrogenation pathway associated with BH-MFD.…”
Section: Introductionmentioning
confidence: 99%
“…Besides factors involved in this study like overall diet composition, further factors will have an influence. Among more detailed nutritional factors is, e.g., starch degradability, which has a direct effect on rumen pH and milk fat as a consequence [31]. As mentioned above, the presence of unsaturated fatty acids in the diet is also considered a nutritional factor of relevance.…”
Section: Discussionmentioning
confidence: 99%